Schooling by design : mission, action, and achievement - Wiggins, Grant P., 1950-; McTighe, Jay. (Alexandria, VA : Association for Supervision and Curriculum Development, 2007)
Provides a school reform strategy which focuses on a long-term mission; curriculum and assessment framework; set principles of learning; structures, policies, and staff that follow the mission; ongoing feedback and adjustments; and an effective planning process.
A vision of schooling -- What is the mission of schooling? -- What should curriculum accomplish? -- How should curriculum be re-formed? -- How should teaching be appropriately depersonalized? -- What is the teacher's job when teaching? -- What is the teacher's job when not teaching? -- What is the job of an academic leader? -- A plan for schooling by design -- How should backward design apply to school reform? -- What are the desired results of school reform? -- What evidence should we collect? -- What actions should we plan? -- What habits must we confront?
Includes bibliographical references (p. 273-277) and index.
Reference and Research Book News.
Professional
Keywords: Curriculum planning -- United States; Education -- United States -- Aims and objectives; Educational change -- United States; School improvement programs -- United States; Curriculum planning -- United States; Education -- Aims and objectives; School improvement programs